Academic resilience and a relationship to the performance of the handstand skill College of Physical Education and Sports Science for Girls, University of Baghdad - سارة صلاح; Dr. Zina Abdulsalam (الرياضة المعاصرة)
The importance of the research lies through the use of the academic resilience scale, which expresses the psychological state that spoke about the students and their ability to perform the handstand skill for the third stage students in the College of Physical Education and Sports Sciences for Girls - University of Baghdad.The problem of the research is that the psychological state that the students go through through performing the handstand skill and through the follow-up and observation of the researchers for the students’ performance, they found an imbalance in the performance of the handstand skill due to the pressures and difficulties they face in performing this skill, so the researchers decided to study resilience The academic steadfastness that the female students enjoy through performing the handstand skill, so the research problem emerged with the following question: What is the nature of the academic resilience that the female students enjoy and its relationship to the performance of the handstand skill for third-year students in the College of Physical Education and Sports Sciences for Girls - University of Baghdad. The study aimed to identify the relationship between academic resilience and its relationship to the performance of the handstand skill among third-year students in the College of Physical Education and Sports Sciences - University of Baghdad. The research sample was chosen as the whole research community and was divided into samples (the exploratory experiment sample, the preparation sample and the main experiment sample) and they were tested on the Academic Resilience Scale and the Handstand Test in Technical Gymnastics and after processing the results it was found that the sample of the research enjoys A level of academic resilience through the performance of the skill of standing on the hands.